Relative contributions of diet and sunshine to the overall vitamin D status of the grazing ewe - Smith, B S; Wright, H (Veterinary record, 1984)
Circulating concentrations of 25-hydroxyvitamin D2 (25OHD2) and 25-hydroxyvitamin D3 (25OHD3) provide, respectively, a measure of the contributions of the diet and sunshine to the overall vitamin D status. These indices were measured in grazing sheep over a 16 month period which included their first pregnancy. Seasonal fluctuations in 25OHD3 concentrations were very marked, demonstrating both the dominance of photobiosynthesis as a source of vitamin D in the summer and also the lack of an effective storage mechanism. The concentration of 25OHD2 was subject to much smaller fluctuations, but when young grass was being consumed it was significantly lower than when mature grass or hay was fed. Supplementation in winter maintained circulating concentrations at a satisfactory level and may be a wise precaution in practice.